2012
DOI: 10.1021/jp304932g
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering of Whole Human Blood, Blood Plasma, and Red Blood Cells: Cellular Processes and Bioanalytical Sensing

Abstract: SERS spectra of whole human blood, blood plasma, and red blood cells on Au nanoparticle SiO 2 substrates excited at 785 nm have been observed. For the sample preparation procedure employed here, the SERS spectrum of whole blood arises from the blood plasma component only. This is in contrast to the normal Raman spectrum of whole blood excited at 785 nm and open to ambient air, which is exclusively due to the scattering of oxyhemoglobin. The SERS spectrum of whole blood shows a storage time dependence that is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
185
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(217 citation statements)
references
References 69 publications
18
185
2
1
Order By: Relevance
“…Biomolecular exosomal components were identified at 1123 cm -1 (lipids + proteins), 1172 cm -1 (proteins), 1307 cm -1 (proteins + lipids), 1366-1370 cm -1 (phospholipids + carbohydrates), 1445 cm -1 (lipids + proteins) and 1572-1576 cm -1 (nucleic acids). Interestingly, most of these pronounced peaks have previously been identified by others when recording Raman spectra of biological samples like erythrocytes [45] or even EVs (by classic Raman or SERS on bulk isolates). [18,19,32,33,36] Next, we could show that the generated spectra, in combination with a PLS-DA classification model, allow us to separate between vesicles derived from B16F10 melanoma cells and RBCderived vesicles.…”
Section: Discussionmentioning
confidence: 73%
“…Biomolecular exosomal components were identified at 1123 cm -1 (lipids + proteins), 1172 cm -1 (proteins), 1307 cm -1 (proteins + lipids), 1366-1370 cm -1 (phospholipids + carbohydrates), 1445 cm -1 (lipids + proteins) and 1572-1576 cm -1 (nucleic acids). Interestingly, most of these pronounced peaks have previously been identified by others when recording Raman spectra of biological samples like erythrocytes [45] or even EVs (by classic Raman or SERS on bulk isolates). [18,19,32,33,36] Next, we could show that the generated spectra, in combination with a PLS-DA classification model, allow us to separate between vesicles derived from B16F10 melanoma cells and RBCderived vesicles.…”
Section: Discussionmentioning
confidence: 73%
“…Reported studies applied to blood serum [77] for the detection of gastric [78,79], colorectal [80], pancreatic [81] and naso-pharyngeal cancers [82] highlight the interest and potential of such approaches. However, the use of nano-particles or appropriate metallic based substrates [83] is required, and while the approach is promising, reproducibility in the data collected remains a challenge [84].…”
Section: Discussionmentioning
confidence: 99%
“…205 Similar phenomena were reported in 2012, when Premarisi et al showed that the SERS spectrum of whole blood had a storage time-dependence that was not evident in the conventional Raman spectroscopy of whole blood. 50 Forensic Science. Raman spectroscopy of blood has not been solely concerned with the biochemical, biological, and medical domains, as it has also been developed as a forensic tool.…”
Section: Whole Bloodmentioning
confidence: 99%
“…50 One of the co-authors of the latter study (McNaughton) was a member of the Monash group who were responsible for much of the earlier work on the oxygenation/deoxygenation cycle. The following year he was involved in another SERS study that characterized the interaction between nanoparticles and hemoglobin/RBCs, 51 and the year after that he co-authored work on hemoglobin's non-fundamental Raman modes; 52 enhanced overtones were observed in spectra of RBCs that, interestingly, were not found in hemoglobin solutions.…”
mentioning
confidence: 99%
See 1 more Smart Citation